(untitled) (The International Journal for Scientific Research, 2025)
In light of the rapid developments in the civil engineering sector, steel structures have emerged as fundamental structural elements in bridge projects, high-rise towers, and industrial buildings. With the increasing scale of projects and the complexity of dynamic loads, challenges related to reliability assessment and quality control in design and execution have also intensified. This study aims to provide a comprehensive scientific approach to employing applied statistics as a modern method for analyzing the distribution of field data related to steel properties and examining factors influencing the structural behavior of steel structures through variance analysis, multiple regression, and probabilistic simulation. The paper relies on selected data from existing construction projects and published experimental models while comparing results with global code standards such as AISC and Eurocode 3. The analysis results demonstrate that integrating statistical methods with numerical modeling contributes to reducing design deviations, thereby enhancing safety factors and reliability.